2020
DOI: 10.1093/mnras/staa990
|View full text |Cite
|
Sign up to set email alerts
|

Infrared luminosity functions and dust mass functions in the EAGLE simulation

Abstract: We present infrared luminosity functions and dust mass functions for the EAGLE cosmological simulation, based on synthetic multi-wavelength observations generated with the SKIRT radiative transfer code. In the local Universe, we reproduce the observed infrared luminosity and dust mass functions very well. Some minor discrepancies are encountered, mainly in the high luminosity regime, where the EAGLE-SKIRT luminosity functions mildly but systematically underestimate the observed ones. The agreement between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 144 publications
4
36
0
Order By: Relevance
“…This has been variously attributed to the lack of 'bursty' star formation in the E model (Furlong et al 2015), or to the strength of the AGN feedback (Katsianis et al 2017b). Whatever the cause, we speculate that the lack of highly star-forming galaxies is the primary reason for the corresponding dearth of bright 850 µm sources in E , as has recently been suggested by Baes et al (2020). Indeed, the discrepancy between E 's SFRF and IR observations at SFR> 100 M yr −1 is broadly similar to the discrepancy seen in their 850 µm number counts at 850 > 1 mJy.…”
Section: Contribution To the Star Formation Rate Functionsupporting
confidence: 59%
See 1 more Smart Citation
“…This has been variously attributed to the lack of 'bursty' star formation in the E model (Furlong et al 2015), or to the strength of the AGN feedback (Katsianis et al 2017b). Whatever the cause, we speculate that the lack of highly star-forming galaxies is the primary reason for the corresponding dearth of bright 850 µm sources in E , as has recently been suggested by Baes et al (2020). Indeed, the discrepancy between E 's SFRF and IR observations at SFR> 100 M yr −1 is broadly similar to the discrepancy seen in their 850 µm number counts at 850 > 1 mJy.…”
Section: Contribution To the Star Formation Rate Functionsupporting
confidence: 59%
“…A large fraction of galaxies in S have a higher DTM , particularly at < 5. This may explain in some part the general offset in infrared luminosity functions seen in the E model at > 1 (Baes et al 2020). [0.12, 0.2, 0.5, 0.8, 1.7, 3.2, 4.5, 6.7].…”
Section: Dust-to-metal and Dust-to-gas Ratiosmentioning
confidence: 87%
“…Dust masses were estimated using modified blackbody fits to synthetic infrared luminosities at FIR wavelengths (160, 250, 350 and 500 μm) generated using a postprocessing 3D radiative transfer procedure (Baes et al 2011;Camps & Baes 2015;Camps et al 2016Camps et al , 2018. Similarly to the results of this study, in the local universe (z < 0.1), Baes et al (2020) found that they could reproduce the shape and normalization of the DMF fairly well, getting very good agreement with the DMFs found by Dunne et al (2011) and Beeston et al (2018) for dust masses M d < 2 × 10 7 M but predicting too few galaxies at higher masses.…”
Section: Comparison With Eaglementioning
confidence: 95%
“…Recently, Baes et al (2020) derived DMFs out to z = 1 for galaxies from the EAGLE simulation. Dust masses were estimated using modified blackbody fits to synthetic infrared luminosities at FIR wavelengths (160, 250, 350 and 500 μm) generated using a postprocessing 3D radiative transfer procedure (Baes et al 2011;Camps & Baes 2015;Camps et al 2016Camps et al , 2018.…”
Section: Comparison With Eaglementioning
confidence: 99%
See 1 more Smart Citation